Equations » Square root equations

To solve square root equations follow these steps:

1. Isolate the square root; so put the root form separate or use substitution as in example 3.
2. Square the left-hand side and the right-hand side of the equation.
3. Check whether the solutions of the squared equation are also solutions of the original equation.

Example 1
square root(8x+1) =  3x 
(square root(8x+1))2 = (3x)2
 8x + 1 = 9x2
–9x2 + 8x + 1 = 0 
D = 82 – 4 · –9 · 1 = 100
x = –8 + square root(100)2 · –9 or x = –8 – square root(100)2 · –9
x = –19 or x = 1

Check:
Only x = 1 is a good solution when filling it in into the original equation.

Example 2
2x – square root(x) = 10
2x – 10 = square root(x)
(2x – 10)2 = (square root(x))2
4x2 – 40x + 100 = x 
4x2 – 41x + 100 = 0 
D = (–41)2 – 4 · 4 · –100 = 81
x = –(–41) + square root(81)2 · 4 or x = –(–41) – square root(81)2 · 4
x = 614 or x = 4

Check:
Only x = 614 is a good solution when filling it in into the original equation.

Example 3
x5 – x2 · square root(x) = 2 
x5 – x2 · square root(x) – 2 = 0 
x5 – x2 · x0.5 – 2 = 0 
x5 – x2.5 – 2 = 0 
Substitute: p = x2.5
p2 – p – 2 = 0 
(p + 1)(p – 2) = 0
p = –1 or p = 2
x2.5 = –1 or x2.5 = 2
x = (–1)12.5 or x = 212.5
x = –1 or x ≈ 1.32

Check:
Only the solution x ≈ 1.32 is correct when used in the original equation.

Do you want an exact solution instead of x ≈ 1.32?

x2.5 = 2 
(x2.5)2 = 22
x5 = 4 
x = fifth root(4)


To top